(untitled) (CIPEEX, 2025)
The actions adopted in the financial sector are increasingly focused on Environmental, Social and Governance (ESG) criteria, where considering technological advances, sustainable finance directs capital towards activities that promote positive impacts on the environment and society, in contrast to traditional financial approaches. This study presents an integrative literature review on the subject of ESG applied to Fintechs (Financial Technology), with a bibliographical, exploratory and qualitative approach. The research aimed to identify and discuss the main academic contributions on the relationship between ESG and Fintechs, as well as to observe how the technological innovations promoted by these companies can contribute to a more sustainable economy. The literature was analyzed by searching the CAPES journal portal and the BVS, Scielo and Web of Science databases, including articles published between 2020 and 2024, in English and Portuguese, using the descriptors ESG, fintech, sustainability and financial technology, using the Boolean indicators and or. In addition, all types of resources that were not articles were excluded from the search, as were articles whose subject matter was not aligned with the topic covered in this research, resulting in a total of 11 selected studies. The analysis revealed that social influence, intensified by ESG factors, is an element that drives technology adoption in the banking sector. The results showed that the integration of ESG and Fintech is an emerging theme that has been addressed by researchers and financial professionals. The discussion on the importance of ESG metrics and their evolution in the financial sphere shows a commitment to the UN’s Sustainable Development Goals, especially goals 8 and 9, which aim to promote inclusive and sustainable economic growth in a way that supports technological development, increasing access to information and communication technologies. Therefore, it can be inferred that by incorporating ESG principles and metrics into fintech business models, such as the development of sustainable investment solutions and green loans, it is possible to democratize access to financial services, reduce carbon emissions through digitalization, and use emerging technologies (such as blockchain and AI) to track and monitor ESG indicators. The research also includes future opportunities for studies and the direction of research on the topic, highlighting the need for a more integrated approach between sustainability and financial technology.